Characterization and prebiotic activity in vitro of inulin-type fructan from Codonopsis pilosula roots. (1st August 2018) - Fu, Yu-Ping; Li, Li-Xia; Zhang, Bing-Zhao; Paulsen, Berit Smestad; Yin, Zhong-Qiong; Huang, Chao; Feng, Bin; Chen, Xing-Fu; Jia, Ren-Rong; Song, Xu; Ni, Xue-Qin; Jing, Bo; et al.
Highlights: The optimum extraction of inulin-type fructan from the roots of C. pilosula was obtained. The detailed structural information of inulin-type fructan was described. The inulin-type fructan could be utilized by different strains of lactobacilli. Abstract: The inulin-type fructan was obtained by DEAE anion exchange chromatography from C. pilosula Nannf. var. modesta (Nannf.) L. T. Shen, after optimized extract condition, which was established by response surface methodology, designed using Box-Behnken factorial design and the optimum condition were: extracting 2.5 h with ratio of solvent to material 40 mL/g at 100 °C, twice. The maximum extraction yield was 20.6 ± 0.2%. It was confirmed as β-(2-1) linkage fructan, with terminal glucose, and with a degree of polymerization of 2–17 (DPav = 6), shown by the results of methanolysis, methylation, nuclear magnetic resonance and molecular weight determination. The prebiotic activity was proven on account of stimulation effect on Lactobacillus and pH reduction of medium in vitro . The results indicated that the inulin from C. pilosula could be used as a potential natural source of prebiotics.